Principles of Curriculum Development in Improving The Quality of PAI Learning: Prinsip Pengembangan Kurikulum Dalam Meningkatkan Kualitas Pembelajaran PAI - Imam Mustofa; Lutfi Fadilah; Anggara Wahyu Widiawati Putri (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
The curriculum of education is always changing and developing according to the needs of education in which all components of the nation also provide encouragement for education providers aiming to always carry out the process of improvement. For this reason, the implementation of the curriculum must have guidelines that must be adhered to. To overcome the above problems, the principles of curriculum development can be used as guidelines for the delivery of education. In this article, the speaker uses a type of library research method, namely in obtaining data from library documents such as books, books, magazines, journals and other documents. Literature study is a form of research related to the way of collecting research materials and data. The data collection technique used is the documentation method, namely by collecting and analyzing documents. The result of this research is that in implementing the curriculum, it is necessary to have guidelines that can be used as guidance. And among the 9 principles of developing the existing curriculum, each education provider is good to be applied in accordance with the existing institutional conditions.